Sickness unto Death in the Age of 24/7: Wolfgang Herrndorf's Arbeit und Struktur - Lilla Balint (Studies in 20th & 21st Century Literature, 2016)
How does one die in the digital age? In exploring this question, this article juxtaposes Jonathan Crary’s critique of the contemporary and Wolfgang Herrndorf’s Arbeit und Struktur—a blog in which the German author documented his three-year battle against brain cancer. The digital age, Crary argues in 24/7, not only enables but forces its natives to ceaselessly engage in work. From the vantage point of terminal illness, however, the digital administration of the self appears not as a strategy of disempowerment but as a life-sustaining practice that allows for the continuous production of the self under precarious bodily conditions. Drawing on the temporality of the digital—its immediacy—the article also examines the poetics of Herrndorf’s blog as illness narrative.
Keywords: digital age; digital writing; illness; narrative